Analisis Minat Mahasiswa pada Program Indonesian International Student Mobility Awards (IISMA) di Program Studi Kosmetik dan Perawatan Kecantikan Universitas Negeri Jakarta - Fatma Zahra; Aniesa Puspa Arum; Dwi Atmanto (Masyarakat Ekonomi Syariah Bogor, 2025)
This research is a quantitative research conducted based on the low participation of students of the Cosmetics and Beauty Care Departement batch 2022-2023 in the Indonesian International Student Mobility Awards (IISMA) program. The purpose of this study was to determine the level of student interest in the IISMA program. The research method used is descriptive quantitative. Respondents in this study were 40 active students from the Cosmetics and Beauty Care Departement, batch 2022-2023. Data collection techniques involved questionnaires, and the data were analyzed using descriptive statistical methods. The analysis results show that the average percentage of overall student interest in the IISMA program is 75%, categorized as “Moderately interested.” Analysis of interest based on year of class obtained results, the interest of 2022 students in the IISMA program has a percentage of 72.5% with the category “Moderately Interested” while in the 2023 class, student interest in the IISMA program has a percentage of 78% with the category “Interested”. The analysis of student interest based on aspects obtained results: aspects of attitude (75%), motivation (86%), talent (65%), educational environment (71%), peers (76%), and family (76%). It can be concluded that the initial interest of the students of the Cosmetics and Beauty Care Departement in the Indonesian International Student Mobility Awards (IISMA) program is still at the stage of situational interest, triggered by external factors, but has not yet developed into a long-term individual interest.